Whistleblowing System Dalam Memutus Rantai Fraud Untuk Mewujudkan Economic Growth (Studi Pada Direktorat Jenderal Pajak Indonesia) - Musmulyadi Musmulyadi; Fitri Indah Sari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The Purpose of this study is to see and know the wistleblowing of goverment systems in breaking the fraud chain in the DJP environment. As we know that fraud is an action that can be used for many parties. Particulary in The DJP enviroment will greatly affect the economy, which means it comes from taxes. Fraud on the DJP is now beginning to be overcome with the invention or mare wistleblowing system aplication by the finance ministry to prevent fraud. This app is created to keep the privacy and privacy whistleblower of fraud. This whistleblowing system aplication was created to break the chain of fraud. This research was conducted by using the metod of studying journals and document related to the theme of search, or in accordance whit the theme of research.